2007
DOI: 10.1007/s00428-007-0372-0
|View full text |Cite
|
Sign up to set email alerts
|

Study of the reactive dendritic cells in small B-cell lymphoproliferations of the skin

Abstract: Distinguishing between low-grade primary cutaneous B-cell lymphoma (LG-pCBCL) and cutaneous lymphoid hyperplasia (CLH) based on histological features is often difficult. CLH lesions contain numerous reactive cells of the histiocyte lineage [Langerhans cells (LC), dermal dendritic cells (DDC), and macrophages], which are also often present in CBCL. The aim of this study was to determine whether immunohistochemical detection of those cells could help differentiate between CLH and LG-pCBCL. We determined the perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Cutaneous lymphoid hyperplasia contains numerous reactive cells of the histiocytic lineage (Langerhans cells, dermal dendritic cells, and macrophages). 27,29 This was also demonstrated in our study by immunostaining for S-100 protein, CD1a, and CD68. Interestingly, only FXIIIa1 cells were recently shown to be significantly increased in CLH compared with low-grade primary CBCL.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Cutaneous lymphoid hyperplasia contains numerous reactive cells of the histiocytic lineage (Langerhans cells, dermal dendritic cells, and macrophages). 27,29 This was also demonstrated in our study by immunostaining for S-100 protein, CD1a, and CD68. Interestingly, only FXIIIa1 cells were recently shown to be significantly increased in CLH compared with low-grade primary CBCL.…”
Section: Discussionsupporting
confidence: 77%
“…Interestingly, only FXIIIa1 cells were recently shown to be significantly increased in CLH compared with low-grade primary CBCL. 27 S-100-, CD1a-, and CD68-positive cells were not found to be a discriminating histologic feature, although the authors did not indicate the histologic features and subtypes of their 16 CLH cases.…”
Section: Discussionmentioning
confidence: 73%
“…As discussed by Kazakov et al and several other authors, the diagnosis of PCMZL can be challenging and can erroneously include cases with pseudolymphomatous reactions. [13][14][15][16] This may mean that several patients were diagnosed with pseudolymphoma, especially between 1990 and 1999, and were therefore not seen as lymphomas in our department. Concerning the pattern of CBCL subtypes, international data are discordant.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated almost no CD1a staining in the infiltrates of CBCLs in contrast to pseudolymphomas and suggested that this fact could help distinguishing these two disorders 21 . In contrast, in other studies no difference could be found between cutaneous pseudolymphomas and B‐cell lymphomas 10,22 …”
Section: Introductionmentioning
confidence: 89%